Perancangan Sistem Informasi Rekapitulasi Data Surat Perintah Membayar Bulanan pada Dinas Bina Marga dan Penataan Ruang Provinsi Jawa Barat - Rosalina, Resmi Ranti; Saputra, Muhammad Iqbal; Abdussalaam, Falaah (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to design a web-based system that uses qualitative methods, namely by conducting interviews and direct observation to collect data and the waterfall method is also used to develop software. Apart from that, PHP is used as a programming language and MySQL as database management. The results of this research conclude that the existence of a web-based information system in the Department of Highways and Spatial Planning of West Java Province can make it easier to help record records efficiently by being designed in such a way and to suit the needs of users in working, especially in the Department of Highways and Marga. West Java Province Spatial Planning for better performance.